Peran Modal Sosial Pada Industri Kacang Sangrai UD.Merpati Di Desa Tombasian Atas Kecamatan Kawangkoan Barat - Rambitan, Dina Mirakel; Ngangi, Charles Reijaaldo; Pangemanan, Paulus Adrian (Sam Ratulangi University, 2024)
The purpose of the study was to determine and describe the role of social capital (trust, social norms, social networks) in the roasted peanut industry UD.Merpati in Upper Tombasian Village, West Kawangkoan District. The research was conducted for 2 months, from October to November 2023. This research was conducted at UD.Merpati roasted peanut industry in Tombasian Atas Village, West Kawangkoan District, Minahasa Regency. The data used in this study are primary data obtained through observation activities at the research location and direct interviews using questionnaires that have been prepared. Secondary data were collected through written sources, mainly in the form of archives and including relevant books on opinions, theories, journals and other supporting books related to the research studied as reference material for research. The sampling method used is purposive sampling, deliberately determined in the roasted peanut industry with a total of 10 respondents, namely workers and owners of the UD.Merpati roasted peanut industry. The data analysis used in this research is descriptive data analysis using a Likert scale. The results showed that the role of social capital is quite good in the UD.Merpati roasted peanut industry in Tombasian Atas Village, West Kawangkoan District. The highest social capital is found in the social network indicator, followed by indicators of trust and social norms. The high level of social capital allows the UD.Merpati Roasted Peanut Industry to survive until now and bring good changes to the industry.